Can the earnings fixation hypothesis explain the accrual anomaly? - Shi, Linna (2013)
This paper provides empirical evidence on whether the earnings fixation hypothesis can explain the accrual anomaly originally documented in Sloan (1996). Our analytical model yields the prediction that if investors fixate on reported earnings, the effectiveness of the accrual strategy will increase in the responsiveness of the stock price to earnings and the differential persistence of cash flows relative to accruals. Our empirical evidence confirms our prediction and lends support to the earnings fixation hypothesis.